ANALISIS TINGKAT KEPUASAN KARYAWAN TERHADAP KOMPENSASI YANG DIBERIKAN PERUSAHAAN (STUDI KASUS DI PERUSAHAAN KOPI BANYUATIS) - Mahatma Tuningrat, Ida Ayu; Satriawan, I Ketut; Sri Lestari, I Gusti Ayu (PIRAMIDA, 2012)
This research aims to know the level of employees satisfaction, influence of compensation variables and which variable that may influence the level of employees satisfactory, also to know the position of each compensation variable toward level of employees satisfaction in Kopi Banyuatis Company. One of method that’s applied in this research was survey method. Data of this research were collected by spreading the questionnaire to 48 chosen respondents. The test which is done in this research, there are validity test, reliability test, index of satisfaction test, F test, and importance performance analysis. Result of the research shows that the level of employees satisfactory is as high as 82,43 percent toward variable of company compensation. The twelve chosen variables are very significantly influenced toward the level of employees satisfactory. Position of each variable which included in quadrant I are: the variable of company policy, responsibility of manager toward their task, chance for employees to pray, variable of comfortable working environment, comfortable working area, amount of salary, amount of employees social security, amount of holiday allowances, working uniform, rights leave fulfillment, and dispensation for illness, and self training & developing for employees.
Keywords: employees satisfaction; variables of compensation; index of satisfaction analysis